Low-cycle fatigue test and life assessment of carbon structural steel GB Q235B butt joints and cruciform joints. Issue 3 (February 2019) - Fang, Zhao; Li, Aiqun; Shen, Sheng; Li, Wanrun
Axial low-cycle fatigue tests are conducted on transverse butt joint specimens and cruciform joint specimens made of carbon structural steel GB Q235B. The effect of slip between the specimens and the grips of the test machine is considered by the proposal of a linear slip model. The cyclic softening properties are studied by observing the variation of stress amplitude with cycles. The cyclic stress–strain curve and the strain–life curve for both kinds of specimens are obtained based on the fatigue test data, and the corresponding coefficients are fitted. In order to verify the fatigue test results, finite element models of specimens are established and the corresponding fatigue life assessment is conducted using the local stress–strain approach and the equivalent structural stress approach, respectively. The results show that the effect of slip is unneglectable and the established linear slip model is reasonable. The two kinds of specimens both show a strain softening property, but cruciform joint specimens experience sudden falls of stress amplitude during the test due to the damage of welded lines; cruciform joint specimens show an either one-side failure mode or two-side failure mode while butt joint specimens only show a one-side failure mode; the two-side failure mode tends to lead to shorter fatigue life, so in the design of cruciform joint, such failure mode should be avoided.